Why they eat, what they eat: patterns of wild edible plants consumption in a tribal area of Western Himalaya - Deepika Thakur; Alpy Sharma; Sanjay Kr. Uniyal (BMC, 2017)
Abstract Background From time immemorial, wild plants have been used for edible purposes. They still continue to be a major source of nutrition for tribal people. However, unfortunately, their use is now declining. This has implications in food security, narrowing genetic base, and future leads. The present study was, therefore, carried out in Chhota Bhangal region of Western Himalaya to analyze uses of wild edible plants (WEP) and the motivations behind their use or abandonment. Methods Field surveys were conducted to the study area from January 2016 to March 2017. Household surveys, group discussions, free listing, and structured questionnaires were used to elicit information on WEP. WEP use was categorized into six categories (vegetables, fruits, chutney, flavoring food, raw food, and local brew). Trends of use (continuing, decreasing, increasing, and not used) and motivations (environmental, economic, sociocultural, agriculture and land use practices, and human-wildlife conflict) behind their use were analyzed. Results Fifty plant species were used by the local people for edible purposes under six WEP categories. Mean and median of WEP used per respondent was 22.3 and 21, respectively. Highest number of these were used as vegetable (mean 8.9) while lowest were used as brew (mean 0.4). Out of the 50 WEP used, 20 were prioritized for motivation analyses. Though plant use is still maintained in the area, changes are evident. Almost 50% of the respondents revealed that they still continue the use of WEP while 36% reported trends of declining use as compared to 5-10 years back. Close to 10% respondents have stopped consuming WEP now and ~ 3% reported an increase in the use of WEP. Among the WEP categories, use of chutney showed an increasing trend. Sociocultural motivations were found to play a prime role, both, in limiting and promoting WEP use. Taste and aroma were the major sociocultural reasons behind using WEP while modernization and changing lifestyle were the main reasons behind declining use of WEP. Conclusions The study concludes that though use of WEP is still maintained in the area, changes in consumption trends are evident. Sociocultural motivations guided use of WEP in the area.